Sosialisasi Pengelolaan Keuangan Desa Kepada Aparatur Desa Untuk Pemberdayaan Masyarakat Di Desa Belangian Kecamatan Aranio Kabupaten Banjar - Gazali Rahman; Achmad Bayu Chandrabuwono; Difinka Nur Leviana; Mawardah; Mega Mustika Tirtha Rahayu; Muhammad Rifqi; Muhammad Ulul Amry; Nor Nazhah; Sandri Alfandi (Wadah Inovasi Indonesia, 2021)
The purpose of this community service is to carry out programs and activities funded by the village income and expenditure budget, administering village financial transactions using the village accounting model, so as to be able to make transparent and accountable village financial reports. With the enactment of Law Number 6 of 2014 concerning Villages, the village government will obtain large enough funds and must be managed properly and can be accounted for. The method of implementing this activity uses data collection methods to collect data by analyzing the realization of the Village Revenue and Expenditure Budget (APBDes) documents, and conducting interviews with village government officials with the Village Consultative Body (BPD). The data analysis method used is a village accounting model to discuss problems, using an analysis of the village accounting model and existing regulations in the village. Socialization activities using data collection methods are very precise, this is really needed according to the needs of village officials, the impact of this socialization is to increase the knowledge of village officials in managing village finances as well as possible.